Assessing the Impact of Periodontal Disease on Oral Health–Related Quality of Life in Individuals with Different Periodontal Health Status Using OSHIP and OHIP - Süheyla Kaya (Essentials of Dentistry, 2026)
Background: The aim of this study was to compare the discriminatory ability of the Oral and Systemic Health Impact Profile for Periodontal Disease (OSHIP-Perio) and Oral Health Impact Profile-14 (OHIP-14) questionnaires in distinguishing between different periodontal conditions. By evaluating which instrument demonstrates greater sensitivity to disease severity, the aim was to determine which is more effective in assessing the impact of periodontal disease on oral health–related quality of life. Methods: This cross-sectional study included 94 participants classified into 5 periodontal status groups (healthy, gingivitis, and periodontitis stages 1-3). Periodontal parameters and oral hygiene indices were recorded. Participants completed the OSHIP-Perio and OHIP-14 questionnaires. Group differences were analyzed using ANOVA or Kruskal–Wallis tests, followed by appropriate post hoc comparisons. A repeated-measures ANOVA compared OSHIP-Perio and OHIP-14 scores. Statistical significance was set at P < .05. Results: Age, bleeding on probing, and plaque index increased with periodontal disease severity. Mean OSHIP-Perio and OHIP-14 scores increased progressively across stages, but ANOVA showed significant differences only for OSHIP (P = .031), with higher scores in periodontitis stage 2 compared to healthy participants (P = .044). Repeated-measures analysis indicated OSHIP scores were significantly higher than OHIP-14 across all groups (P < .001). While OHIP-14 failed to distinguish between periodontal groups, OSHIP significantly differentiated periodontal health from periodontitis. Gingivitis appeared in both post hoc subsets, reflecting its transitional nature between health and periodontitis. Conclusion: The OSHIP-Perio scale effectively distinguished between periodontal health and periodontitis, highlighting its potential clinical and epidemiological utility. Gingivitis consistently appeared as a transitional stage between health and periodontitis, reflecting its ambiguous clinical nature. While OSHIP-Perio shows promise for identifying clear-cut disease states, its ability to discriminate gingivitis remains limited, suggesting that scale refinement with stage-specific items could improve its sensitivity across the full spectrum of periodontal disease.